2012
DOI: 10.1007/s13280-012-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Ecological Quality Indicators and Biogeochemical Fluxes in the Baltic Sea: A Multi-Model Ensemble Study

Abstract: Multi-model ensemble simulations using three coupled physical-biogeochemical models were performed to calculate the combined impact of projected future climate change and plausible nutrient load changes on biogeochemical cycles in the Baltic Sea. Climate projections for 1961-2099 were combined with four nutrient load scenarios ranging from a pessimistic business-as-usual to a more optimistic case following the Helsinki Commission 0 s (HELCOM) Baltic Sea Action Plan (BSAP). The model results suggest that in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 32 publications
3
115
0
1
Order By: Relevance
“…The ensemble mean for SSS only shows small deviations from the observations. Together with the quality analysis in Meier et al (2012), we conclude that the performance of the ensemble simulations in the control period is sufficient for the present analysis.…”
Section: Control Periodmentioning
confidence: 72%
See 2 more Smart Citations
“…The ensemble mean for SSS only shows small deviations from the observations. Together with the quality analysis in Meier et al (2012), we conclude that the performance of the ensemble simulations in the control period is sufficient for the present analysis.…”
Section: Control Periodmentioning
confidence: 72%
“…However, two ECHAM5-based scenarios are also scaled down by the regional CLM model instead of the RCAO model (Table 1), which therefore increases the number of regional models in the ensemble. Meier et al (2012) found that overall conclusions do not depend on the weighting of particular simulations in this ensemble. Altogether, we consider the ensemble as a reasonable composition of global and regional models for the Baltic Sea region.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The ECOSUPPORT work plan was built on the confidence of models' capacity to simulate the changing climate, and included the following aspects: (i) the assessment of predictive skills of the models by comparing observed and simulated past climate variability (i.e., quantification of model uncertainties) and analyzing causes of observed variations (e.g., Gustafsson et al 2012;Meier et al 2012;Niiranen et al 2012), (ii) the performance of multi-model ensemble simulations of the marine ecosystem for 1850-2100, forced by reconstructions of the past climate (e.g., Gustafsson et al 2012;Ruoho-Airola et al 2012) and various future greenhouse gas emission scenarios and airand river-borne nutrient load scenarios (ranging from a pessimistic business-as-usual to the most optimistic case) (e.g., Arheimer et al 2012;Eilola et al 2012;MacKenzie et al 2012;Meier et al 2012;Neumann et al 2012), (iii) the analysis of projections for the future Baltic Sea ecosystem, using a probabilistic approach accounting for uncertainties caused by biases of regional and global climate models, lack of process description in state-of-the-art ecosystem models, unknown greenhouse gas emissions and nutrient loadings as well as natural variability (e.g., Arheimer et al 2012;MacKenzie et al 2012;Meier et al 2012;Neumann et al 2012;Niiranen et al 2012), (iv) the assessment of climate change impacts on the marine biota, like effects of ocean acidification (e.g., Havenhand 2012), biodiversity and fish populations with focus on cod, sprat and herring (e.g., MacKenzie et al 2012;Niiranen et al 2012), (v) a socioeconomic impact assessment (e.g., Piwowarczyk et al 2012), (vi) the generation of a freeaccess data base of scenario model results and tools to access the database with the help of a decision support system (DSS) 2 and finally (vii) the dissemination of project results to stakeholders, decision makers and the public (see below).…”
Section: Objectivesmentioning
confidence: 99%
“…Sea level rise of *1.7 mm year -1 in the southern BSR and -9.4 mm in the Gulf of Bothnia (in the northern Baltic Sea, land uplift still overcompensates for sea level rise) will also contribute to environmental change in the region (HELCOM 2007). Higher temperatures will likely cause more frequent algal blooms, also influenced by possibly larger nutrient loads to the sea caused by heavier rains (e.g., Meier et al 2012). Low-lying coastal areas will be even more exposed to erosion during expected mild winters, with strong and frequent storms in the absence of sea-ice cover.…”
Section: Introductionmentioning
confidence: 99%